Abnormal Gray Matter Structural Networks in Idiopathic Normal Pressure Hydrocephalus - Yin, Le-Kang; Zheng, Jia-Jun; Tian, Jia-Qi; Hao, Xiao-Zhu; Li, Chan-Chan; Ye, Jian-Ding; Zhang, Yu-Xuan; Yu, Hong; Yang, Yan-Mei (Frontiers in Aging Neuroscience, 2018)
Purpose: Idiopathic normal pressure hydrocephalus (iNPH) is known as a treatable form of dementia. Network analysis is emerging as a useful method to study neurological disorder diseases. No study has examined changes of structural brain networks of iNPH patients. We aimed to investigate alterations in the gray matter structural network of iNPH patients comparing with normal elderly. Materials and Methods: Structural networks were reconstructed using covariance between regional gray matter volumes extracted from three-dimensional T1-weighted images of 29 possible iNPH patients and 30 demographically similar normal-control (NC) participants and compared with each other. Results: Global network modularity was significantly larger in the iNPH network (P < 0.05). Global network measures were not significantly different between the two networks (P > 0.05). Regional network analysis demonstrated eight nodes with significantly decreased betweenness located in bilateral frontal, right temporal, right insula and right posterior cingulate regions, while only the left anterior cingulate was detected with significantly larger betweenness. Hubs of the iNPH network were mostly located in temporal areas and the limbic lobe, that of the NC network were mainly located in frontal areas. Conclusions: Network analysis was a promising method to study iNPH. Increased network modularity of iNPH group was detected here, and modularity analysis should be paid more to explore the biomarker to select shunting responsive patient.